Comparison and analysis of the techniques and tactics of Zhang Jike using new plastic ball and celluloid ball in the match - Chiwen, S.; Tong, Z.; Nan, G.; Ling, Z. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
As a result of rapidly changing the ball material in table tennis competition. It has brought great challenge to the table tennis players` technique and tactics. It is necessary to understand the impact of material changes in the ball on players' technique and tactics. This paper based on the methods of video observation and mathematical statistics, this paper makes a systematic technical and tactical analysis of Zhang Jike's six games in London 2012 which used the celluloid balls, and 2016 Rio Olympics which use the new plastic balls. It is in order to find out the impact on Zhang Jike`s technique and tactics by using the celluloid balls and the new plastic balls. The results shown that after using the new plastic table tennis, Zhang Jike's technique and tactics had little change, but the technical quality was decreased, and the continuous attack ability was obviously decreased.